Toxicological Analysis’s Importance in Treating Acute Poisoning Patients with Unclear Exposure Histories - Pushpa Parkash, Tehreem Abaid, Talha Naeem Cheema, Ahmad Raza Khurram, Nadir Ali, Afsheen Siddiqi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Examining the clinical features of patients with acute poisoning whose exposure history was ambiguous from a toxicological analysis standpoint was the purpose of this study. Methods: This descriptive study was comprised of 140 patients. Inclusion criteria were patients who had toxicological testing done and whose exposure histories were unclear. Clinical symptoms and toxicant categories were examined. Results: Among 140 cases, 105 cases has positive toxicological results and 35 cases had negative. Majority of the cases had age 31-40 years. Frequency of males were 86 (61.4%) and females were 54(38.6%). Accident was the most common exposure found in 108 (77.1%) cases. Oral was the most common route. Disturbance of consciousness was the most common etiology observed. Among the positive toxicological patents, the most common types of compounds were sedatives, insecticides, herbicides, and psychiatric pharmaceuticals. Conclusion: Acute poisoning can present with a wide variety of nonspecific symptoms in individuals whose exposure history is unclear; in these cases, toxicological testing is essential for making a diagnosis or ruling out other possible causes. Keywords: Toxicological analysis, Clinical manifestation, Acute poisoning